Enhancing Self-Learning in Chemistry: A Literature Review and the Role of Chemistory Explorer - Rahmalan, Hidayah; Mohtar, Syahida; Arbain, Nur Atikah (Journal of Advanced Computing Technology and Application (JACTA), 2024)
This paper presents a comprehensive literature review of the factors contributing to effective self-learning in chemistry. The literature highlights the importance of interactive and engaging learning tools, personalized feedback, historical contextualization, and gamified elements in enhancing self-learning outcomes. "Chemistory Explorer" integrates these key elements through its interactive timeline, virtual laboratories, multimedia content, photo booth, and game puzzle modules. By providing an immersive and personalized learning experience, the platform fosters deeper understanding, critical thinking, and motivation among learners. The study demonstrates best practices of self-learning in chemistry and advances them by leveraging cutting-edge technology to make chemistry education more accessible and effective. This research underscores the platform’s potential to revolutionize self-learning in chemistry and contribute to the broader educational landscape.